Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics: System Demonstrati 2021
DOI: 10.18653/v1/2021.eacl-demos.22
|View full text |Cite
|
Sign up to set email alerts
|

Massive Choice, Ample Tasks (MaChAmp): A Toolkit for Multi-task Learning in NLP

Abstract: Transfer learning, particularly approaches that combine multi-task learning with pre-trained contextualized embeddings and fine-tuning, have advanced the field of Natural Language Processing tremendously in recent years. In this paper we present MACHAMP, a toolkit for easy fine-tuning of contextualized embeddings in multi-task settings. The benefits of MACHAMP are its flexible configuration options, and the support of a variety of natural language processing tasks in a uniform toolkit, from text classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…We split the top-10 among the data splits (i.e., train, development, and test set), and also between source splits (i.e., BIG, HOUSE, TECH). We use the default hyperparameters in MACHAMP (van der Goot et al, 2021) as shown in Table 4. For more details we refer to their paper.…”
Section: Type Of Skills Annotatedmentioning
confidence: 99%
“…We split the top-10 among the data splits (i.e., train, development, and test set), and also between source splits (i.e., BIG, HOUSE, TECH). We use the default hyperparameters in MACHAMP (van der Goot et al, 2021) as shown in Table 4. For more details we refer to their paper.…”
Section: Type Of Skills Annotatedmentioning
confidence: 99%
“…Both the Bi-LSTM (Plank et al, 2016) and the MaChAmp (van der Goot et al, 2021) toolkit are capable of Multi Task Learning (MTL) (Caruana, 1997). We therefore, set up a number of experiments testing the impact of three different auxiliary tasks.…”
Section: Auxiliary Tasksmentioning
confidence: 99%
“…Models are fine-tuned for 100,000 steps with batch size of 16. For downstream tasks, we use MaChAmp (van der Goot et al, 2021) and train our models for 10 epochs. The best checkpoints were selected based on performance on the dev sets.…”
Section: Frameworkmentioning
confidence: 99%

On Language Models for Creoles

Lent,
Bugliarello,
de Lhoneux
et al. 2021
Preprint